A framework for co‐developing conservation research projects with stakeholders: A Lake Victoria case study. Issue 4 (6th December 2020) - van den Broek, Karlijn L.; Luomba, Joseph; Onyango, Horace O.; Musobya, Moses; Klein, Sina A.
Abstract: Stakeholder engagement has increasingly gained popularity in conservation research since it promotes relevant research that has impact and can inform evidence‐based policy. Lake basins can especially benefit from research co‐created with stakeholders since these regions tend to face a multitude of conservation challenges while also dealing with many stakeholders that are directly dependent on a lake's resources. Particularly important for successful, co‐created research is the first phase of stakeholder engagement, namely the co‐development of the research agenda with stakeholders. This phase tends to determine whether or not projects will be funded and implemented, therefore providing a foundation for subsequent realization of a project, as well as the impact of the research findings. The present study provides a framework for the application of stakeholder engagement in co‐developing a research agenda, as illustrated through a case study on Lake Victoria in East Africa, concluding with key lessons learned from this case study.